The adoption of learning experience design tools in classroom planning activity: A systematic literature review - Queiros, Leandro Marques (2021)
Most of the research on Learning Design (LD) focuses on technology to automatically run a sequence of activities proposed to students and facilitated by the educator through computers. One way of thinking about a LD system is as a workflow mechanism for collaborative activities, and a specific learning design is similar to a recipe, however, educational and for teachers - describes ingredients (content) and instructions (process). The aim of this article is to outline the state-of-the-art in Learning Design, covering the period from 2001 to 2018. We analyzed the quality, coverage of topics, research methodologies adopted and the potential impact of LD. We carried out manual and automatic research for Systematic Literature Review (SLR) published in journals and conference proceedings. We investigated the relevant studies, compared and integrated our results with the two previous higher education studies. Therefore, 67 articles were identified, which we classified in two main areas of research: a) The use of the specification and its standards; b) The development of systems of authorship, management and execution of LD. From these 67, only 8 achieved the minimum quality requirements established and were considered relevant for the scenario of this research. Finally, our results allow us to see that the SLR as a research method has been less adopt in the LD research community. Additionally, most SLRs did not assess the quality of primary studies, thus restricting their potential impact on educational practice.